2018
DOI: 10.18203/2319-2003.ijbcp20181642
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing pattern of oral anti-diabetic agents in type 2 diabetes mellitus patients in a tertiary care hospital

Abstract: Background: Prescription pattern studies are a tool for assessing the prescribing, dispensing and distribution of medicines. The main aim of assessing prescribing pattern is to facilitate rational use of medicines. So the main aim of the study was to assess the prescribing pattern of oral anti-diabetic agents in type 2 diabetes mellitus, to assess the rationality of the prescribed drugs and also to assess the pattern of co-morbid conditions associated with type 2 diabetes mellitus in a tertiary care hospital.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…However, men seem more susceptible to DM due to the consequences of obesity as prevalent in this part of country. Similar results were obtained in several studies from India 6,11,12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, men seem more susceptible to DM due to the consequences of obesity as prevalent in this part of country. Similar results were obtained in several studies from India 6,11,12 .…”
Section: Discussionsupporting
confidence: 91%
“…Epidemiological studies have shown that family history of diabetes has a correlation to reduced insulin sensitivity in progenies. Positive family history of DM in patients have been reported in several national as well as international studies as reflected in our study too 6,12,15 .…”
Section: Discussionsupporting
confidence: 78%
“…Additionally, a combination of metformin and glibenclamide (oral) is both easy to administer and affordable to most patients [17]. Several studies have reported a similar trend in the prescription of antidiabetics with biguanides and sulfonylureas being the most frequently prescribed [18][19][20]. High insulin prescription could have been aimed at controlling the abnormally high glucose levels in lately diagnosed patients who fail to respond well to the oral hypoglycaemic.…”
Section: Discussionmentioning
confidence: 99%